Discrete Values of the Coefficient of Damping under Conditions of Explicit Acoustic Nonlinearity - Miškinis, P. (Nonlinear Analysis: Modelling and Control, 2006)
Qualitative analysis of hypersound generation is described by the inhomogeneous Burgers equation in the case of the non-harmonic and arbitrary light field. A qualitative possibility of the appearance of discrete values of the coefficient of extinction of the sound wave and the possibility of generation of the same sound signal by different light fields is shown.
Keywords: evolution equation; integrable system; Burgers equation; acoustics; nonlinearity